Classifying Esophageal Motility by FLIP Panometry: A Study of 722 Subjects With Manometry. (20th December 2021) - Carlson, Dustin A.; Gyawali, C. Prakash; Khan, Abraham; Yadlapati, Rena; Chen, Joan; Chokshi, Reena V.; Clarke, John O.; Garza, Jose M.; Jain, Anand S.; Katz, Philip; Konda, Vani; Lynch, Kristle; et al.
Abstract : INTRODUCTION: Functional luminal imaging probe (FLIP) panometry can evaluate esophageal motility in response to sustained esophageal distension at the time of sedated endoscopy. This study aimed to describe a classification of esophageal motility using FLIP panometry and evaluate it against high-resolution manometry (HRM) and Chicago Classification v4.0 (CCv4.0). METHODS: Five hundred thirty-nine adult patients who completed FLIP and HRM with a conclusive CCv4.0 diagnosis were included in the primary analysis. Thirty-five asymptomatic volunteers ("controls") and 148 patients with an inconclusive CCv4.0 diagnosis or systemic sclerosis were also described. Esophagogastric junction (EGJ) opening and the contractile response (CR) to distension (i.e., secondary peristalsis) were evaluated with a 16-cm FLIP during sedated endoscopy and analyzed using a customized software program. HRM was classified according to CCv4.0. RESULTS: In the primary analysis, 156 patients (29%) had normal motility on FLIP panometry, defined by normal EGJ opening and a normal or borderline CR; 95% of these patients had normal motility or ineffective esophageal motility on HRM. Two hundred two patients (37%) had obstruction with weak CR, defined as reduced EGJ opening and absent CR or impaired/disordered CR, on FLIP panometry; 92% of these patients had a disorder of EGJ outflow per CCv4.0. DISCUSSION: Classifying esophageal motility in response to sustained distension with FLIP panometry parallels the swallow-associated motility evaluation provided with HRM and CCv4.0. Thus, FLIP panometry serves as a well-tolerated method that can complement, or in some cases be an alternative to HRM, for evaluating esophageal motility disorders.